CHANGING THE BEHAVIOR IN TOOTH BRUSHING IN STUDENTS OF SIXTH GRADE OF SDN 6 MAS, KECAMATAN UBUD, KABUPATEN GIANYAR - I Nyoman Gejir; I Gede Surya Kencana; Ni Made Widhiasti (Jurnal Kesehatan Gigi (Dental Health Journal), 2013)
The regular prevention from accummulation of plaque is the best method to avoid periodontal deaseases. The important preventive action is to brush the teeth effectively. This method is the main method to remove plaque. The objectite of this study is to change the behavior in brushing teeth among the sixth year student of SDN 6 Mas, Kecamatan Ubud , Kabupaten Gianyar through coaching strategy and instructions and monitoring by the students' porents. The research design  of this study is action research in this case is the action of brushing teeth with a respondens of 35 person, the data collection has been through interview and observation. The finding of this research shows that in the first cycle it was found that 62% of the responden had incorrect behavior with regard to the time of brushing their teeth.71,4% of the respondents had incorrect behaviors in the movement of brushing their teeth. Their average score of OHI-S in the first cycle was 2.03 (medium category). In the second cycle, it was found that no respondent had incorrect behaviors with regard to the time of brushing their teeth, and there still 31.1% of the respondents had incorrect movements in brushing their teeth. Their average score of OHI-S in the second cycle  was 1.26 (medium category). In the third cycle, it was found that no respondents had incorrect behavior in brushing their teeth. Their average score of OHI-S in the 0.94 (good category). The result of the evaluation of the dental cleanliness and oral cleanliness of the respondents os compared between  before and after the actions had a correlation rate of 0.586 and a significance rate of 0.000. Based on the research fnding, it can be concluded that the coaching with instructions and monitoring by students' parents can change the behavior of the students of sixth year of SDN  6 Mas, Kecamatan Ubud, Kabupaten Gianyar in brushing their teeth. With regard to this finding, it is suggested that the parents should always monitor the children to brush their teeth at home.